INTERIOR DESAIN UNTUK MENINGKATKAN KENYAMANAN DAN AKSESIBILITAS PADA PENATAAN RUANG PERPUSTAKAAN KOTA BOGOR - Dewi Astuti; Rakhmanita, Rakhmanita; Sumaiyah Fitrian Dini (Jurnal Ilmiah Teknik, 2025)
The Bogor City Library plays an important role in creating a strong literacy ecosystem, functioning as a center for community empowerment by providing access to information and skills development. This research aims to analyze circulation patterns and spatial planning in libraries, in order to increase public interest in utilizing existing facilities. Although founded in 1972, the library faced serious challenges, including inadequate space and unattractive facilities, such as a non-functioning multimedia room and a lack of private rooms for discussions. The low literacy rate in Bogor City shows the need for more efforts to increase interest in reading. It is hoped that the "Free Literacy" program can be a solution, but its success is very dependent on library development. By implementing modern architectural designs and innovative elements, libraries can create a comfortable and inspiring learning environment. This research is expected to provide constructive recommendations for developing libraries as effective and inclusive literacy centers. Focusing on the quality of space and human circulation patterns will support optimal visitor experience, making libraries the main pillars in improving literacy and the quality of life of people in the city of Bogor. The synergy between attractive facilities, inspiring space quality, and efficient circulation design will strengthen the role of libraries in social, economic and cultural development.